Interferensi Fonologis Bahasa Prancis Terhadap Bahasa Indonesia Oleh Mahasiswa Sastra Prancis Universitas Negeri Semarang Berdasarkan Jenis Kelamin Dan Tingkat Semester - Berliana, Nova; Santoso, Wahyudi Joko (Universitas Pahlawan Tuanku Tambusai, 2024)
In French language learning, phonological interference still frequently occurs among students at various semester levels. This study aims to identify which vowel sounds experience phonological interference and why students still encounter such interference. The research adopts a deductive approach, starting from a hypothesis and then attempting to validate it through analysis or experimentation. The vowel sounds examined in this study are French vowels [a], [ɑ], [e], [ɛ], [i], [o], [ɔ], [u], [y], [ə], [œ], [ø] in French vocabulary in initial, medial, and final positions. Data sources are obtained from students majoring in French Literature at Semarang State University, from the 2021 and 2022 cohorts or the third and fifth semesters, with the number adjusted according to the male student population in the classes. The method and technique for data analysis involve the articulatory phonetic correspondence method with speech organ determinants. The basic technique used is the determinant element sorting technique with the advanced technique of sorting determinant elements (PUP). The researcher will also employ the comparison linking technique (HBS) if there is equivalence between the pronunciation of French vowel sounds produced by respondents and those produced by the Larousse online dictionary. The vowel sound that experiences the most phonological interference is the pronunciation of [ə] (mid-central unrounded vowel) as [ɛ] (mid-front unrounded vowel) in initial word positions, with a percentage of 50%. Based on gender, male students experience more phonological interference compared to female students. The percentage of phonological interference among male students is 70% by respondents RL3, RL5, RL6, RL7, RL8, RL9, RL10, while for female students, it is 60% by respondents RP1, RP5, RP6, RP7, RP8, RP10. The percentage of interference per vowel sound in the 2021 cohort is 42%, while in the 2022 cohort, it is 58%.